Application of carbonized ion exchange resin beads as catalyst support for gas phase hydrogenation processes - Prekob Ádám; Hajdu Viktória; Muránszky Gábor; Kocserha István; Bela Fiser; Fiser Béla; Фішер Бейло; Viskolcz Béla; Vanyorek László (Akadémiai Kiadó, 2020)
Abstract. Carbonized ion exchange resin beads were prepared as catalyst for gas phase hydrogenation processes. Amberlite IR 120 polystyrene based sulfonated ion exchange beads were carbonized at 900 °C. The process of carbonization was monitored by FTIR combined thermogravimetric analysis. During the carbonization formed sulfur dioxide, carbon dioxide and organic compounds. The carbon pearls were used as catalyst support for Pd nanoparticles. The catalyst was characterized by scanning electron microscopy and X-ray difractometry. The diameters of the palladium nanoparticles on the catalyst surface were between 15 and 50 nm, but bigger aggregates were also detected. The catalyst was tested during the gas phased heterogeneous catalytic hydrogenation of 1-butene. The hydrogenation process was followed by FTIR measurements, 93% conversion was reached after 10 min.
Editorial board: https://link.springer.com/journal/11144/editorial-board
Contents: https://link.springer.com/journal/11144/volumes-and-issues/129-1
Keywords: Resin beads; Carbonization; Gas phased hydrogenation